Mitochondrial DNA origin of indigenous Malagasy chicken: implication for a functional polymorphism at the Mx gene - Razafindraibe, H.; Mobegi, V.A.; Ommeh, S.C.; Ralptondravao; Bjornstad, G.; Hanotte, Olivier H.; Han Jianlin (Wiley, 2008)
We report the mitochondrial DNA (mtDNA) characterization of 77 indigenous chickens (fighting and meat birds) from Madagascar, using DNA sequences of the first hypervariable segment of the D-loop. Comparison with reference samples from the African continent and Asia revealed two mtDNA haplogroups, suggesting a dual geographic and genetic origin for the indigenous Malagasy chickens. The most common haplogroup was present in 65 individuals of the two types; it is likely of Indonesian origin. The second haplogroup was observed in 12 fighting birds and meat chickens; it could be of African continental origin and/or the result of recent introgression with commercial lines. We further studied a G/A single nucleotide polymorphism at nucleotide position 1892 bp of the coding sequence of the Mx gene that is reported to be one of the candidate susceptible/resistant genes to viral infection in chicken. Our results indicate the "susceptible" allele G is the most common with frequencies of 65% and 70% in Malagasy fighting and meat chickens, respectively. However, the allelic frequency difference between the two types of chickens is not significant (P > 0.05). These results are discussed in light of our current linguistic and archaeological knowledge on the origin of indigenous Malagasy chickens.